Effect of Responsiveness and Communication Clarity on Revisit Intention Through Service Timeliness Among Inpatients - Rini Rubiyanti; Andry Andry; Idrus Jus’at (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Hospital service quality is a primary determinant in shaping patient loyalty, particularly revisit intention. This study aims to analyze the effect of responsiveness and communication clarity on revisit intention, with timeliness of service as an intervening variable among inpatients. The research employed a quantitative approach with a cross-sectional design. The sample consisted of 162 inpatients selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM-PLS). The results indicate that responsiveness and communication clarity have a positive and significant effect on revisit intention. Communication clarity significantly affects timeliness of service, whereas responsiveness does not have a significant effect on timeliness of service. Timeliness of service does not directly affect revisit intention; however, it partially mediates the relationship between communication clarity and revisit intention. These findings emphasize that the quality of healthcare providers’ communication is a dominant factor in shaping inpatient loyalty. The research implications highlight the importance of strengthening clinical communication and service time management as strategies to improve hospital service quality.